CONJUNCTION IN EFL STUDENTS' HORTATORY EXPOSITION WRITINGS: AN SFL PERSPECTIVE ON STUDENTS' WRITINGS - Fania Shafira Irsalina, - (2018)
This paper reports on the results of a study that examined the conjunction in EFL learners' writings, both in the draft and final draft of Hortatory Exposition Text written by eleventh graders of a senior high school in Bandung. This study also looked at the impact of feedback provided in the students' two versions of writing. A qualitative research methodology was utilized to reveal the cohesion and the effect of feedback in the writing of two groups of students. Altogether, eighteen essays on Hortatory Exposition tasks written by nine students were analyzed using Halliday and Matthiessen (2004) theory of Conjunction. The result of the study indicated that all three types of conjunction, namely Elaboration, Extension and Enhancement were found in students' writing. It was found that the utilization of conjunction plays important roles: to emphasize and illustrate the subsequent sentence, to enhance the logical connection between parts of the text systemically, and to connect preceding part with the next sequentially. The use of conjunction was already demonstrated in the students' draft; then, after the students' draft was given feedback, it was found that the feedback improved to some extent the students' appropriate use of conjunction. It was revealed that most of the students responded positively toward the feedback given to them.